Impact of twisting rate in 10 pairs of unshielded twisted-pair copper cables on insertion loss and crosstalk coupling for G.fast technology - Saizalmursidi Md Mustam; Mohammad Arif Ilyas; Muhammad Syukri Mohd Yazed; Che Ku Afifah Che Ku Alam (Bulletin of Electrical Engineering and Informatics, 2020)
An ultrafast digital subscriber line (DSL) technology called G.fast is important for ultrafast broadband Internet access services. In G.fast, the existing cable bundles installed for 250 m from the distribution point to the customer’s premises are used to support the gigabit data transmission (aggregated 1 Gbit/s) for frequency up to 106 MHz or 212 MHz. Since unshielded cable is used, and the frequency is 12 times higher compared to the very high-speed DSL2 (VDSL2), it is important to investigate the cable performance in terms of insertion loss and crosstalk coupling. In this paper, the impact of cable twisting rate on 10 pairs of unshielded twisted-pair copper cables for a small copper bundle on insertion loss and crosstalk coupling is investigated. A simulation model is developed based on the standard cable installed in Malaysia. The model reliability is validated by comparing the obtained result with the published result in the literature. Besides, the twisting rate of 100 m cable is manipulated by changing its lay size to determine its impact on insertion loss and crosstalk coupling. The results showed that a high twisting rate can reduce the far-end crosstalk but increase both the insertion loss and near-end crosstalk.